Alih Kode dan Campur Kode dalam Interaksi Mahasantri Putri Mahad Al-Jamiah IAIN Curup - Amanah, Nisa Ul; Botifar, Maria; Khair, Ummul (ESTETIK : Jurnal Bahasa Indonesia, 2021)
This study aims to describe the form of code switching, code mixing and speech events in the interaction of female students of Mahad Al-Jamiah IAIN Curup. The type of research used was field research using a qualitative descriptive approach. The data were taken in January-March 2021. The method used was the listening method and its follow-up techniques, namely tapping techniques, free speaking listening techniques, conversational engagement listening techniques, recording techniques, and note-taking techniques. The data were analyzed by identifying, classifying, interpreting, describing and presenting research results. The results showed that there was internal and external code switching. There are seven languages used in communication, namely Bengkulu Malay, Javanese, Rejang language, Rawas Malay, Semende language, Palembang Malay, and English. Second, the discovery of code mixing events, namely internal and external code mixing. There were six languages used at the time of the code mixing, namely Javanese, Rejang, Rawas Malay, Palembang Malay, English and Arabic. Third, speech events in the interaction of female students of Mahad Al-Jamiah IAIN Curup from 45 speech data, were Settings and scenes, Participants, Ends, Act sequences, Key, Instrumentalities, Norm of interaction and interpretation, and Genres